Nexus between police attitudes and responses to domestic and family violence in Australia: does training matter? - Md. Jahirul Islam (Policing and society, 2022)
Police attitudes, knowledge, and beliefs about domestic and family violence (DFV) are crucial for promoting a sense of safety and security for victim-survivors seeking criminal justice support and protection. Using survey data collected from a statewide sample of police officers (N = 243) in one jurisdiction in Australia, this study investigates the influence of police attitudes toward DFV on their decision-making in relation to providing support services, taking proactive actions, and seeking domestic violence protection order (DVO) applications in response to DFV. This study further examines whether the receipt of DFV training as well as confidence in handling aspects of DFV moderate police response to DFV situations. Based on multivariate logistic regression adjusted models, police officers who had proactive attitudes (e.g. pro-arrest attitudes) were more willing to provide support services and take other actions, whereas those who possessed reactive attitudes (e.g. minimum police involvement attitudes) were less likely to seek DVO applications and take other actions. Moreover, both training and confidence in handling aspects of DFV cases had a moderating effect such that the likelihoods of making DVO applications, taking other actions, and providing support services are substantially and significantly higher among officers who have received DFV training and have confidence in handling cases. Police attitudes about DFV appear instrumental in shaping responses to victims and survivors of DFV. These findings reinforce the importance of increasing access to officers’ training for DFV as well as finding opportunities to strengthen officers’ confidence in responding to DFV.